Shaping regionality in socioeconomic systems : late Hellenistic-late Roman ceramic production, circulation, and consumption in Boeotia, Central Greece (c. 150 BC-AD 700) - Peeters, Dean, (Roman and late antique Mediterranean pottery ;, 2023)
This volume sheds some necessary light on local economies from the (late) Hellenistic to the Late Roman period. The concepts of regions and regionality are employed to explore the complexity of ancient economies and (ceramic) variability and change in Boeotia (Central Greece), largely on the basis of the survey data generated by the Boeotia Project for Thespiae, Askra, Hyettos, Tanagra and their surroundings. The analysis illustrates the existence of a range of (micro-)regions within Boeotia that are characterised by patterns and differences in ceramic production, variable intensities of interaction in larger networks, and consumer preferences and/or variability in aspects of consumption.